(untitled) (Aporte Santiaguino, 2019)
The research had as objectives to identify the characteristics of the territory and the indicators that influence the structural vulnerability of the houses to the simian risk . In the methodology, the non-experimental transectional design was applied, using as a tool a questionnaire for the application of surveys to the sample of 343 dwellings; The Analysis Hierarchical Process (AHP) was used to determine the level of vulnerability of the houses. The findings show that the territory of the Chucchun sub-basin, due to the characteristics of the lithology, slope and susceptibility or exposure, presents conditions of high and very high vulnerability; the results of the surveys show that the houses present conditions of vulnerability and before the occurrence of the seismic risk, the houses are highly vulnerable